Social capital configuration, legal bonds and performance in buyer–supplier relationships - Carey, Sinéad; Lawson, Benn; Krause, Daniel R. (Journal of Operations Management, 2011)
AbstractAcademics have increasingly recognized the benefits derived from social networks embedded within companies’ buyer–supplier relationships. However, prior research has only examined the influence of social capital elements on performance, either individually or in part. We propose an integrative model examining the relationships among relational, structural and cognitive dimensions of social capital, and between these dimensions and the cost and innovation performance of the firm. A sample of 163 buyer–supplier relationships is used to test the model. Regression results indicate that the relational dimension of social capital fully or partially mediates the effect of the cognitive dimension on performance, and partially mediates the link between the structural dimension, operationalized as social interaction ties, and innovation performance. Further, high levels of legal bonds were found to moderate the relationship between the relational dimension of social capital and performance outcomes. Implications for theory and managers are discussed.